Dessert box product: review finding and its potential development in Aceh - Maulinda, Maulinda; Widayat, HP; Jaya, R (PT FORMOSA CENDEKIA GLOBAL, 2024)
Nowadays, dessert boxes are a popular food and important product that has been recognized in a new market. One of the problems during production of the dessert box is the quality of the product, particularly: mouth-feel sensation and effect of the using local fruit.The objective of this research was to describe the state of the art about this topic and future research issues. The number of papers analyzed about 30 articles published from 2010–2020. The articles were obtained from scientific providers such as Science direct, EBSCO, Cross-Reff, Researchgate, DOAJ, Academia.Edu, and Google Scholar. In this research, we cluster substance research to two items such as state of the art dessert box and potential development in Aceh Province. The content analysis was used to describe the state of the arts and novelty. The results of the study show that it is critical for the dessert box producer to apply a new product based on local fruit in Aceh. Synthesis and determination of main topics of research in the future is undertaken at the end.